Radio Programme on Managing Banana Bacterial Wilt - Yiga, Sirajje (Technical Centre for Agricultural and Rural Cooperation, 2008)
This script features recommendations for the control of Xanthomonas (pronounced ?zanthomonas') bacterial wilt in bananas. Bacterial wilt poses a significant threat to banana production in Uganda.